2020
DOI: 10.1007/s13197-020-04513-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packaging materials and storage conditions on the microbial quality of pearl millet sourdough bread

Abstract: Sourdough is one of the oldest methods of cereal fermentation applied mainly for the sole purpose of baking and has been proven to enhance the production of microbiologically safe products. This study investigated the effect of packaging materials and storage conditions on the microbial quality and some intrinsic parameters of the sourdough bread. Pearl millet flour was naturally fermented for 72 h to obtain sourdough which was used with pearl millet flour to produce sourdough bread while the control bread was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As storage days increased, the moisture content of bread samples decreased. This could be due to moisture migration from the bread crumb to the bread crust followed by environment, which promotes mold growth and leads to successive increase as the storage days increases (Martins et al, 2021). The bread crust absorbs some of the water, while the majority of the water migrates from the crumb to the atmosphere, resulting in water loss during storage (Monteau et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As storage days increased, the moisture content of bread samples decreased. This could be due to moisture migration from the bread crumb to the bread crust followed by environment, which promotes mold growth and leads to successive increase as the storage days increases (Martins et al, 2021). The bread crust absorbs some of the water, while the majority of the water migrates from the crumb to the atmosphere, resulting in water loss during storage (Monteau et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The SOD method is long, and the fermentation process produces large amounts of organic acids, ethanol, and other important metabolites that have positive effects on the texture of the product and the aging rate. 8 The prefermented dough method is usually referred to as the sponge dough (SPD) method and is conducted by mixing and fermenting part of the flour, water, and yeast immediately to form a sponge-like structure, followed by mixing with the remaining dough components. Like the SOD method, the SPD method requires a longer fermentation time than the STD method, but it generally produces bread with better aroma and flavor, higher volume, and better texture qualities than the STD method.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous SOD fermentation, one of the oldest biological processing techniques, usually relies on the presence of naturally occurring microorganisms, such as yeast and lactic acid bacteria (LABs), whose fermentation activity plays an important role in the quality of SOD bread. The SOD method is long, and the fermentation process produces large amounts of organic acids, ethanol, and other important metabolites that have positive effects on the texture of the product and the aging rate 8 . The pre‐fermented dough method is usually referred to as the sponge dough (SPD) method and is conducted by mixing and fermenting part of the flour, water, and yeast immediately to form a sponge‐like structure, followed by mixing with the remaining dough components.…”
Section: Introductionmentioning
confidence: 99%
“…So, these are best consumed at room temperature, but it has a short shelf life (2–3 days) due to high water activity (Upasen & Wattanachai, 2018). Several studies have reported the use of bio‐nanocomposite film like carboxymethyl cellulose‐chitosan ‐ZnO (Martins et al, 2021), starch‐chitosan, and nanoclay (Jha, 2020) for elongation of shelf life of the bread.…”
Section: Introductionmentioning
confidence: 99%
“…It was stated that Aspergillus niger, Cladosporium, Rhizopus nigricans, Neurospora sitophila, Pichia anomala, and Candida parapsilosis were the most popular fungi responsible for the spoilage of bakery products. However, bread is more susceptible to bacterial and fungal growth at ambient temperature or more as compared to bread stored at refrigerated conditions (Martins et al, 2021), but low temperature shows a high level of undesirable starch retrogradation which is responsible for staling (Xi et al, 2022). So, these are best consumed at room temperature, but it has a short shelf life (2-3 days) due to high water activity (Upasen & Wattanachai, 2018).…”
Section: Introductionmentioning
confidence: 99%